Effects of Gaseous Ozone (O3) on Artificial Population and Aflatoxin B1 Production by Aspergillus flavus in Stored Whole Cinnamon in Iraqi Markets - Diyaa Aljaza (Institute of Medico-legal Publications Pvt Ltd, 2020)
Stored whole cinnamon can become contaminated with aflatoxins.For public health requirements cinnamonshould be produced free of AFB1or bellow EU legislation limit (5µg/kg), soin this study, examined theefficacy of different concentrations (0, 300 and 600 ppm) of ozone on fungal populations (CFU) and AFB1production of A.flavus on stored whole cinnamon at three aw levels (0.92, 0.94&0.96 aw) at 25?C and exposuretime (60 min). In general, the results presented in this study showed that the populations AFB1 produced ofA.flavusin artificially contaminated whole cinnamon were significantly affected by O3treatment.